Cardiac auscultation poorly predicts the presence of valvular heart disease in asymptomatic primary care patients. Issue 22 (24th May 2018) - Gardezi, Syed K M; Myerson, Saul G; Chambers, John; Coffey, Sean; d'Arcy, Joanna; Hobbs, F D Richard; Holt, Jonathan; Kennedy, Andrew; Loudon, Margaret; Prendergast, Anne; Prothero, Anthony; Wilson, Joanna; et al.
Abstract : Objective: Cardiac auscultation is a key clinical skill, particularly for the diagnosis of valvular heart disease (VHD). However, its utility has declined due to the widespread availability of echocardiography and diminishing emphasis on the importance of clinical examination. We aim to determine the contemporary accuracy of auscultation for diagnosing VHD in primary care. Methods: Cardiac auscultation was undertaken by one of two experienced general practitioners (primary care/family doctors) in a subset of 251 asymptomatic participants aged >65 years undergoing echocardiography within a large community-based screening study of subjects with no known VHD. Investigators were blinded to the echocardiographic findings. Newly detected VHD was classified as mild (mild regurgitation of any valve or aortic sclerosis) or significant (at least moderate regurgitation or mild stenosis of any valve). Results: Newly identified VHD was common, with mild disease in 170/251 participants (68%) and significant disease in 36/251 (14%). The sensitivity of auscultation was low for the diagnosis of mild VHD (32%) but slightly higher for significant VHD (44%), with specificities of 67% and 69%, respectively. Likelihood ratios were not statistically significant for the diagnosis of either mild or significant VHD in the overall cohort, but showed possible value for auscultation in non-overweight subjects (body mass index <25 kg/m 2 ). Conclusion: Cardiac auscultation has limited accuracy for the detection of VHD in asymptomatic patients and is a poor diagnostic screening tool in primary care, particularly for overweight subjects. Ensuring easy access to echocardiography in patients with symptoms suggesting VHD is likely to represent a better diagnostic strategy.